PERCEIVED DIGITAL INTERACTIVE LEARNING MEDIA AND MOTIVATION AS OVERLAPPING CORRELATES OF SELF-REPORTED ECONOMICS OUTCOMES - Rizaldi Alwari; Sjeddy Watung; Edwin Wantah; Jerry Wuisang (EDUCATIONE, 2026)
Digital learning experiences and student motivation are frequently modeled as distinct correlates, although their measures may capture overlapping perceptions. This study examined the bivariate and joint associations of perceived digital interactive learning media and learning motivation with self-reported economics outcomes among Grade 10 students at one Indonesian secondary school. A cross-sectional survey analyzed 106 students from a population of 144; the source record identified simple random sampling but did not document randomization, participant demographics, or non-response. Three 15-item summed Likert scales were used. Internal consistency was exceptionally high (Cronbach's alpha = .981-.983), warranting caution regarding redundancy and discriminant validity. Simple regressions showed strong associations for digital media (beta = .832, R-squared = .693, p < .001) and motivation (beta = .833, R-squared = .694, p < .001). The joint model was significant, F(2, 103) = 118.313, p < .001, R-squared = .697, but unique coefficients were not significant for digital media, B = .396, 95% CI [-.372, 1.164], p = .308, or motivation, B = .437, 95% CI [-.325, 1.199], p = .258. The increment beyond the stronger single-predictor model was only delta R-squared = .003. The pattern is compatible with substantial shared variance, overlapping item content, or common-method effects and does not establish an integrated mechanism or causal influence. The study offers a school-specific diagnostic for refining measurement and digital pedagogy. Future research should report complete sampling and ethics procedures, use objective achievement data and non-overlapping validated scales, and provide multicollinearity, residual, and longitudinal or experimental evidence.